HUMANITARIZATION OF ENGINEERING EDUCATION - Vasily N. Stegny (Высшее образование в России)
The paper describes the process of realization of the concept of engineering education humanitarization by means of a special organizational form – the faculty of humanities at technical university. The faculty has worked out the unified system of humanities and socio-economic disciplines such as economics, philosophy, sociology, political science, jurisprudence, domestic history, culturology, foreign languages, for all faculties and specialties. The article presents the main tendencies of faculty development, the results of its research activities, the place and the role of the faculty in university life during 20 years of its existence.